Glass Ceiling Sebagai Hambatan Dalam Mewujudkan Keadilan dan Kesetaraan Gender Bagi Perempuan Pekerja - Azwar Azwar (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
This paper discusses the phenomena of the glass ceiling, which affects women's chances of obtaining professional jobs, as well as its connection to issues of equality and equity in regards to gender. A literature review of several scientific studies that address the glass ceiling is used as the method of writing for this method. The findings of this literature review indicate that the